PERANAN POLRI DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN DENGAN KEKERASAN DI WILAYAH HUKUM POLRES PAYAKUMBUH - Anny Yuserlina (Ensiklopedia Social Review, 2020)
Crime in Indonesia in recent years has often been questioned by academics, the public and legal practitioners. One form of crime that has the highest frequency is theft. From there lies the big role of law enforcement officials in combating crime for the sake of creating public order. In general, the social problems that arise due to violent theft are felt to be very disruptive to people's lives, especially in the Payakumbuh Police jurisdiction. In essence, the problem is a shared responsibility. So the role of the Police in tackling criminal acts of theft with violence in the Legal Area of the Payakumbuh Police, but its role is not yet effective because in this case there are still found inhibiting factors to the role of the Police, so that the role of the Police is not effective.